2014
DOI: 10.1186/2049-3258-72-42
|View full text |Cite
|
Sign up to set email alerts
|

Determinant of factors associated with child health outcomes and service utilization in Ghana: multiple indicator cluster survey conducted in 2011

Abstract: BackgroundThe effects of National Health Insurance Scheme in Ghana and its impact on child health outcome and service utilization cannot be underestimated. Despite the tremendous improvement in child health care in Ghana, there are still some challenges in relation to how National health insurance membership, socioeconomic status and other demographic factors impacts on child health outcomes. The study seeks to determine the association between NHIS membership, socio-economic status, geographic location and ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 18 publications
4
30
0
Order By: Relevance
“…2) Traditional in this study means traditional/spiritualist/no religion. What factors influence of Dwumoh et al [12] who revealed that health insurance of children influenced full immunization of children in Ghana and those of Immurana and Urma [11] with regard to demand for the Measles 2 vaccine for children in Ghana.…”
Section: Regression Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2) Traditional in this study means traditional/spiritualist/no religion. What factors influence of Dwumoh et al [12] who revealed that health insurance of children influenced full immunization of children in Ghana and those of Immurana and Urma [11] with regard to demand for the Measles 2 vaccine for children in Ghana.…”
Section: Regression Resultsmentioning
confidence: 99%
“…In Ghana, Immurana and Urma [10], Immurana and Urma [11], Dwumoh et al [12], Matthews and Diamond [13], Bosu et al [14], McGlynn [15], and Duah-Owusu [16] have also conducted studies on factors that influence immunization utilisation.…”
Section: Introductionmentioning
confidence: 99%
“…Also belonging in the rich index by mother was found by Lakew et al (2015) to be one of the determinants of full immunization of children in Ethiopia. On Ghana, it has been found that children membership of National Health Insurance Scheme (NHIS), mother's education and geographical location determined full immunization of children (Dwumoh et al (2014). Also antenatal care was found to increase the odds of immunization among children (McGlynn, 2012).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Logullo et al (2008) found that, age, region, education and marital status were not related with taking measles vaccines adequately in Sao Paulo city of Brazil. Specifically on Ghana, Dwumoh et al (2014) using data from the 2011 Ghana Multiple Indicator Cluster Survey found that mother's education, National Health Insurance Scheme (NHIS) membership of children and geographical location influenced full immunization of children. McGlynn (2012) found in Ghana that, antenatal care increased the odds of immunization among children in Ghana using the 1998, 2003, and 2008 GDHS.…”
Section: Review Of Literaturementioning
confidence: 99%